Using scale and human agency to frame ranchers' discussions about socio-ecological change and resilience. (December 2022) - Greene, Christina; Wilmer, Hailey; Ferguson, Daniel B.; Crimmins, Michael A.; McClaran, Mitchel P.
Abstract: Resilience is becoming the dominant discourse in research and policy on climate change as well as wider social-ecological change. Resources and assets alone are often not enough to support resilience, especially in the context of multi-scalar change. Human agency, that is the ability to act and make choices that produce desirable outcomes, is critical to responding and thriving in the face of social-ecological change, however agency remains underexplored in the social-ecological change and resilience literature. We use a local knowledge approach to understand the role of human agency in shaping resilience to complex multi-scalar social-ecological changes. This research draws on focus groups and interviews with ranchers and land managers in seven different focal landscapes across the American West to understand how ranchers articulate social-ecological change in western rangelands, how they describe their own agency in responding to such changes, and how local knowledge of agency and social-ecological change can strengthen conceptions of resilience. Ranchers expressed more agency in addressing observed ecological and climatic changes but less agency in navigating multi-scalar sociological, political and land use changes as these processes unfold at scales far beyond the ranch. Several ranchers also provided examples where scale jumping or increasing community human agency created pathways for resilience to multi-scalar processes. This analysis has two main implications for resilience interventions. First, resilience is a complex negotiation of interconnected and multi-scalar processes and climate resilience cannot be separated from other ongoing economic and social processes. Second, human agency is a critical component of resilience that allows for negotiations of multi-scalar social-ecological changes. Highlights: Explores cattle ranchers' local knowledge of social-ecological change and resilience. Resilience shaped by changes in ecology, economics, community, and rangeland users. Ranchers voiced more agency with ecological changes over other dimensions. Resilience involves adaptation to interconnected and multi-scalar processes. Increasing human agency can open paths for resilience to multi-scalar changes.